Golding’s Lord of the Flies: Human Liberation into Savagery - Bhatta, Arjun Dev (DMC Research Journal, 2024)
The term ‘savagery’ cannot have a general and universal definition. However, it refers to the human state of brutality and uncivilization that can be exhibited by individuals or groups anywhere anytime. Golding’s Lord of the Flies depicts human nature which is inherently savage and evil. This article aims to analyze how the civilized preadolescent school children who have been evacuated on an uninhabited island during the Second World War degenerated from the state of civilization into savagery. I have analyzed savage instincts prevalent specifically in the antagonist Jack and his deadly tribe. It also states that humankind’s removal of the rudimentary values signifies their regression into savagery and brutality. Thus, human liberation into savagery as represented by Jack and the other boys of his clan is the focus of this study. Mankind’s inherent savagery has been discussed in detail concerning the plot, images, symbols, and characters in this article. This study hopes to bring insight into human behavior and make a harmonious relationship in human society.